MK5: On Coordination and Multiple Stakeholder Platforms (MSPs). - Gaheb, Kim; Lazarus, Kate (2009)
CPWF Mekong Project 5 is divided into two components, the first relating to coordination, and the second to the development, management and maintenance of multiple stakeholder platforms. Coordination The Basin Leader leads this project team, which is responsible for coherence of the overall BDC research program through ensuring BDC research remains problem-, opportunity- and impact-focused.